Analysis Of Acceleration Affecting Factors during Waiting Time for Outpatient Services at Regional General Hospital (RSUD) Dr. Dradjat Prawiranegara, Serang Regency - Iis Istifaiyatuddianah; Anastina Tahjoo; Nofierni Nofierni (Journal of Multidisciplinary Academic, 2021)
Waiting time is the time used by patients to get health services from the registration point to entering the specialist doctor's examination room. Ideally, the waiting time for an outpatient installation from registration to a doctor's examination is based on the Minimum Service Standard, which is 60 minutes. This study aims to analyse the effect of the length of provision of medical records, Competency of Human Resources, infrastructure and outpatient flow on the acceleration of waiting time for outpatient services at the Regional General Hospital (RSUD) dr. Dradjat Prawiranegara, Serang Regency. The research method is quantitative method with individual research type. Sampling In this study, a non-probability sampling design was used as sampling method. The determination of the respondents who were used as samples was carried out using a purposive sampling method, including of 100 outpatient BPJS patients in 2021. The cross section and primary data were used as the research time and the data source, respectively. For the data analysis using multiple linear regression. The results of this study found the value of F-count (4.631) > F-table (2.46) and sig 0.05 (0.002 0.05) while H0 is rejected and H1 is accepted. It means that there is a significant influence between the provision of medical records, competence of human resources, infrastructure and outpatient flow on the Acceleration of Waiting Time for Outpatient Services at the Regional General Hospital (RSUD) dr. Dradjat Prawiranegara, Serang Regency. On the other hand, the results of the study also found no effect on the Acceleration of Waiting Time for Outpatient Services at the Regional General Hospital (RSUD) dr. Dradjat Prawiranegara Serang Regency, namely the provision of medical records and outpatient flow. The findings in this study indicate that the competence of human resources and infrastructure is the most dominant variable and influences the acceleration of waiting time for outpatient services at the Regional General Hospital (RSUD) dr. Dradjat Prawiranegara Serang Regency